Copayment policy reforms and effective care utilization by patients with persistent asthma in Taiwan - Juan, Tzu-Ling; Chang, Li-Chuan; Lee, Yue-Chune (Health policy (Amsterdam), 2022)
•Copayment reforms influenced effective care for patients with persistent asthma.•The results provide long-term evidence for copayment policy effect.•Copayment reforms should account for the well-being of the economically disadvantage populations. Reforms to the Taiwan National Health Insurance copayment scheme in 2005 imposed a notable increase in the cost of outpatient visits. This provided an ideal situation to determine whether such reforms lead to a reduction in the utilization of effective care by patients with persistent asthma. This study applied the pretest-posttest non-randomized control group design in our analysis of nationwide claims data (2002 to 2010). Based on propensity score matching, the patients were divided into two groups, subject and not subject to copayment reform. Medication Management for People with Asthma measure was used to identify patients with persistent asthma and instances of effective care. Matching yielded a final panel of 7,890 individuals with persistent asthma (3,945 individuals in each cohort) eligible for the study. GEE analysis revealed that policy reforms had significant effects over the short-term (OR = 0.745, p < 0.05), medium-term (OR = 0.752, p < 0.01), and long-term (OR = 0.721, p < 0.01). Reforms to copayment policy were significantly correlated with a reduction in the utilization of effective care by patients with persistent asthma over the short-, medium- and long-term. Government should develop implementation strategies aimed at protecting the economically disadvantaged patients.